Hybridité, animalité et métissage : la littérature francophone contemporaine entre parasitisme et devenir-autre - Marie, Annabelle Corinne (School of Languages and Literatures, 2016)
Postcolonial Francophone literature, as it has evolved since the independence movements in the French colonies (mainly in Africa and in the Caribbean islands), has known two major moments in the 20th century, where it distanced itself from metropolitan French Literature: in the forties, fifties and sixties, with the movement of the « négritude » and more recently, in the nineties, with the rise of "créolité"- which will lead to the actual current of "Littérature-monde" (2005), and corresponds to the era that will be investigated here. It would be naïve to think that this desire for literary independence could have been fulfilled entirely, while expressed in the language of the "oppressor". In spite of its claims to the contrary, this postcolonial francophone literature remains to this day haunted by its French model. To a certain degree, it is still very much dependent as can be seen from its fixation with Paris as the only "centre" of culture and the frequency of themes such as social parasitism and hospitality. But of course, Francophone literature cannot be reduced to such a simplistic model. Its relationship to French Literature can't be reduced to a purely mimetic one. In spite of (or maybe thanks to) its heavy borrowing from the French canon, it has succeeded in creating a new space of reciprocal exchanges and constant metamorphosis. It is this space that H. Bhabha called "third space", defined by hybridity and "métissage" - a paradoxical way of coping with the double inheritance of the same and the other. In opposition to the static behaviour in which the parasite engages when imitating, one has to conceive, according to G. Deleuze and F. Guattari, a heterogeneous relationship characterized by movement and fluctuation: a "becoming" rather than a "being". It is this notion of constantly changing identities that we will analyze in reaction to parasitism, which remains based on imitation: a need for metamorphosis best expressed in "animalisation" and the loss of identity it produces. In order to test this hypothesis, we will analyze a series of works of fiction where this theme of animalisation is most visible (produced over the past 15 years in Postcolonial Francophone literature). Some of the novels in our corpus are the following: Mémoires d'un porc-épic, by Mabanckou (from Congo); Moi, l'interdite, by Ananda Devi (from Mauritius), Temps de chien by P. Nganang (from Cameroun) and Un Chien mort après lui by Jean Rolin (France). We hope that the relative homogeneity of our findings will allow us to formulate new insights in the way Francophone literature deals with those ever returning questions of identity and otherness.